Geochemistry and age of groundwater in the Williston Basin, USA: Assessing potential effects of shale-oil production on groundwater quality. (February 2021) - McMahon, Peter B.; Galloway, Joel M.; Hunt, Andrew G.; Belitz, Kenneth; Jurgens, Bryant C.; Johnson, Tyler D.
Abstract: Thirty water wells were sampled in 2018 to understand the geochemistry and age of groundwater in the Williston Basin and assess potential effects of shale-oil production from the Three Forks-Bakken petroleum system (TBPS) on groundwater quality. Two geochemical groups are identified using hierarchical cluster analysis. Group 1 represents the younger (median 4 He = 21.49 × 10 −8 cm 3 STP/g), less chemically evolved water. Group 2 represents the older (median 4 He = 1389 × 10 −8 cm 3 STP/g), more chemically evolved water. At least two samples from each group contain elevated Cl concentrations (>70 mg/L). Br/Cl, B/Cl, and Li/Cl ratios indicate multiple sources account for the elevated Cl concentrations: septic-system leachate/road deicing salt, lignite beds in the aquifers, Pierre Shale beneath the aquifers, and water associated with the TBPS (one sample). 3 H and 14 C data indicate that 10.8, 21.6, and 67.6% of the samples are modern (post-1952), mixed age, and premodern (pre-1953), respectively. Lumped-parameter modeling of 3 H, SF6, 3 He, and 14 C concentrations indicates mean ages of the modern and premodern fractions range from 1 to 30 years and 1300 to >30, 000 years, respectively. Group 2 contains the highest CH4 concentrations (0.0018–32 mg/L). δ 13 C–CH4 and C1 /C2 +C3 data in groundwater (−91.7 to −70.0‰ and 1280 to 13, 600) indicate groundwater CH4 is biogenic in origin and not from thermogenic shale gas. Four volatile organic compounds (VOCs) were detected in two samples. One mixed-age sample contains chloroform (0.25 μg/L) and dichloromethane (0.05 μg/L), which are probably associated with septic leachate. One premodern sample contains butane (0.082 μg/L) and n-pentane (0.032 μg/L), which are probably associated with thermogenic gas from a nearby oil well. The data indicate hydrocarbon production activities do not currently (2018) widely affect Cl, CH4, and VOC concentrations in groundwater. The predominance of premodern recharge in the aquifers indicates the groundwater moves relatively slowly, which could inhibit widespread chemical movement in groundwater overlying the TBPS. Comparison of groundwater-age data from five major unconventional hydrocarbon-production areas indicates aquifer zones used for water supply in the TBPS area have a lower risk of widespread chemical movement in groundwater than similar aquifer zones in the Fayetteville (Arkansas) and Marcellus (Pennsylvania) Shale production areas, but have a higher risk than similar aquifer zones in the Eagle Ford (Texas) and Haynesville (Texas, Louisiana) Shale production areas. Highlights: Aquifer zones used for water supply dominated by premodern recharge. Chemicals from oil production present in some groundwater but are not widespread. Slow groundwater movement inhibits widespread chemical movement in groundwater. Risk of widespread chemical movement in groundwater ranked using age data.